Primary glottic malignant melanoma: a case series and literature review - Aldaihani, Abdullah; Stewart, Christopher; Aldaihani, Mohammad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Primary glottic malignant melanoma (PGMM) is an exceptionally rare malignancy, with fewer than 30 documented cases in existing literature. Unlike cutaneous melanomas, PGMM typically lacks well-defined risk factors and presents at an advanced stage due to its insidious growth pattern. This study presents a case series of PGMM, emphasizing clinical presentation, histopathological findings, management strategies, and outcomes. Additionally, a comparative literature review highlights the challenges in diagnosis, treatment, and prognosis. PGMM is an exceptionally rare malignancy. Unlike cutaneous melanomas, PGMM typically lacks well-defined risk factors and presents at an advanced stage due to its insidious growth pattern. This study presents a case series of PGMM, emphasizing clinical presentation, histopathological findings, management strategies, and outcomes. A comparative literature review further highlights the challenges in diagnosis, treatment, and prognosis.